The European Union measures taken to prevent and manage the recent migration flows – from survival to social and economic integration of migrants - Victor Nicolăescu; Gabriela Petre (CES Working Papers, 2017)
Migrant's crisis of 2015 affected the credibility of the social security system built and strengthened over the past three decades by the European Union. Adoption of the refugee quotas in order to be relocated by the Member States of the European Union is a current issue that requires at least two directions of analysis: increasing the efficiency of the European Union humanitarian aid addressed to destination countries and deepening the dimensions of the integrative process of social inclusion of migrants. This article proposes to review the state of implementation mechanisms for supporting measures addressed to migration flows developed by the European Union together with candidate states and the mechanisms developed by international institutions and organization in order to provide specific measures of humanitarian assistance to populations in affected areas war.
Keywords: 330; social inclusion; humanitarian assistance; migration; European Union